Hepatic artery injury in a six-year-old patient after laparoscopic cholecystectomy: A management challenge : Hepatic artery injury in pediatric - Akış Yıldız , Zeliha; Su, Şeyma Meliha; İlçe, Zekeriya (Journal of Surgery and Medicine, 2024)
Laparoscopic cholecystectomy is among the most common surgeries in adults and is increasing in the pediatric age group. However, data are lacking on complications of the surgery and their treatment in children. Although many case series can be found that address hepatic artery injury after cholecystectomy in adults, we could not find similar publications in the English literature relating to the pediatric age group. This report shares the complex diagnosis and treatment process of a six-year-old female patient who presented with jaundice eight months after laparoscopic cholecystectomy. During the treatment process, it was observed that the common bile duct went into lysis in the late period due to haptic artery injury. The treatment continued with redo hepaticojejunostomy and catheters passed through the anastomosis line in the patient, who had anastomotic stenosis after hepaticojejunostomy. Twenty-four months after the patient’s first operation, she had no active complaints. Complications may occur months after a cholecystectomy. In this case, arterial injury should be kept in mind. We wanted to contribute by presenting the first case in the literature on hepatic artery injury in the pediatric age group.